Prevalence of aldosterone breakthrough in dogs receiving renin‐angiotensin system inhibitors for proteinuric chronic kidney disease - Marisa K. Ames; Shelly L. Vaden; Clarke E. Atkins; Jean‐Sebastien Palerme; Catherine E. Langston; Gregory F. Grauer; Sarah Shropshire; Christina Bove; Tracy Webb (Journal of Veterinary Internal Medicine, 2022)
Abstract Background The influence of aldosterone breakthrough (ABT) on proteinuria reduction during renin‐angiotensin system (RAS) inhibition for spontaneous proteinuric chronic kidney disease (CKDP) has not been determined in dogs. Objectives Determine whether ABT occurs in dogs with CKDP and if it is associated with decreased efficacy in proteinuria reduction during RAS inhibitor treatment. Animals Fifty‐six client‐owned dogs with CKDP and 31 healthy client‐owned dogs. Methods Prospective, multicenter, open‐label clinical trial. Dogs were treated with an angiotensin‐converting enzyme inhibitor or angiotensin receptor blocker alone or in combination at the attending clinician's discretion and evaluated at 5 time points over 6 months. Healthy dogs were used to determine the urine aldosterone‐to‐creatinine ratio cutoff that defined ABT. The relationship of ABT (present at ≥50% of visits) and proteinuria outcome (≥50% reduction in urine protein‐to‐creatinine ratio from baseline at ≥50% of subsequent visits) was evaluated. Mixed effects logistic regression was used to evaluate the relationship between clinical variables and outcomes (either successful proteinuria reduction or ABT). Results Thirty‐six percent (20/56) of dogs had successful proteinuria reduction. Between 34% and 59% of dogs had ABT, depending on the definition used. Aldosterone breakthrough was not associated with proteinuria outcome. Longer duration in the study was associated with greater likelihood of successful proteinuria reduction (P = .002; odds ratio, 1.6; 95% confidence interval [CI], 1.2‐2.2). Conclusions and Clinical Importance Aldosterone breakthrough was common in dogs receiving RAS inhibitors for CKDp but was not associated with proteinuria outcome.